PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY RATIO, TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Umi Mas 'Ulah (POLITEKNIK LP3I JAKARTA, 2025)
Researchers are trying to understand how certain figures about companies, such as the amount of money they have compared to their debts (known as the Current Ratio), their debts compared to the money deposited by their owners (known as the Debt to Equity Ratio), and how they generate money for their owners (known as Return on Equity), impact their stock prices.We observed food and beverage businesses listed on the Indonesian stock exchange and operating.We want to know whether these figures impact the overall stock price or the individual stock prices.This method is researchDeductive research using a quantitative and descriptive nature.The significant test results (0.000 less than 0.05) indicate that investors look at all financial figures simultaneously.On the other hand, they look at how all those numbers work together to determine how healthy a business is.This study looks at available cash, company debt, and total profit to help explain stock price changes.Investors in the food and beverage stock market from 2020 to 2023 paid more attention to the overall financial picture rather than just looking at one number.During that time, there are other important factors outside the company that might be very significant.